Molecular characterization of the conoid complex in Toxoplasma reveals its conservation in all apicomplexans, including Plasmodium species. - Ludek Koreny; Mohammad Zeeshan; Konstantin Barylyuk; Eelco C Tromer; Jolien J E van Hooff; Declan Brady; Huiling Ke; Sara Chelaghma; David J P Ferguson; Laura Eme; Rita Tewari; Ross F Waller (PLoS Biology)
The apical complex is the instrument of invasion used by apicomplexan parasites, and the conoid is a conspicuous feature of this apparatus found throughout this phylum. The conoid, however, is believed to be heavily reduced or missing from Plasmodium species and other members of the class Aconoidasida. Relatively few conoid proteins have previously been identified, making it difficult to address how conserved this feature is throughout the phylum, and whether it is genuinely missing from some major groups. Moreover, parasites such as Plasmodium species cycle through 3 invasive forms, and there is the possibility of differential presence of the conoid between these stages. We have applied spatial proteomics and high-resolution microscopy to develop a more complete molecular inventory and understanding of the organisation of conoid-associated proteins in the model apicomplexan Toxoplasma gondii. These data revealed molecular conservation of all conoid substructures throughout Apicomplexa, including Plasmodium, and even in allied Myzozoa such as Chromera and dinoflagellates. We reporter-tagged and observed the expression and location of several conoid complex proteins in the malaria model P. berghei and revealed equivalent structures in all of its zoite forms, as well as evidence of molecular differentiation between blood-stage merozoites and the ookinetes and sporozoites of the mosquito vector. Collectively, we show that the conoid is a conserved apicomplexan element at the heart of the invasion mechanisms of these highly successful and often devastating parasites.